HLA-DRB1 the notorious gene in the mosaic of autoimmunity (2017)
The major histocompatibility complex system is the most polymorphic gene cluster of the mammal genome. In humans, this is a genomic locus known as the human leukocyte antigen (HLA) system. The HLA encodes mostly immune-associated proteins whose main effect is the presentation of antigens to the immune cells. Thus, it is clear that it is essential for to the proper function of the immune response against pathogens and strongly implicated in the development of autoimmune diseases. Nonetheless, there are hundreds of polymorphisms of HLA-DRB1 which have been associated with different autoimmune disorders as well as with immune response to infection and vaccines. It is possible that the interaction of specific HLA with pathogenic antigens is one of the keys favoring (or protecting) toward the development of an autoimmune disease. In the era of personalized medicine, it would be of great help to build a map of the genomic risk of each individual to evaluate the risk of developing an autoimmune condition. © 2016, Springer Science+Business Media New York.